Effects of sacubitril/valsartan on cardiac reverse remodeling and cardiac resynchronization in patients with acute myocardial infarction - Yang, Pei; Li, Xiaokang; Wang, Lijin; Wu, Xinlei; Wang, Chiyao; Li, Tian; Wang, Haiyan (Frontiers in Cardiovascular Medicine, 2023)
Introduction In 2014, the PARADIGM-HF trial (Prospective Comparison of ARNI with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure) has shown that sacubitril/valsartan can reduce the risk of hospitalization and death from cardiovascular causes more effectively than enalapril (an ACEI) in heart failure patients with reduced ejection fraction (HFrEF). Similarly, the PARADIGM-HF trial (Comparison of Sacubitril-Valsartan vs. Enalapril on Effect on NT-proBNP in Patients Stabilized from an Acute Heart Failure Episode) came to similar conclusions and extended the PARADIGM-HF trial results in 2019. Since then, numerous new studies have provided further insight in HFrEF, sacubitril/valsartan can reduce N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels, increase left ventricular ejection fraction (LVEF), reverse ventricular remodeling, and reduce other non-fatal manifestations of clinical deterioration as compared to ACEI/ARB. However, few trials have compared the effects of these drugs in patients shortly after AMI. Therefore, it is necessary to further explore the clinical efficacy and safety of sacubitril/valsartan vs. valsartan in patients with AMI. Methods We conducted an open-label, prospective, randomized controlled trial to determine the superiority in ameliorating ventricular remodeling and preventing of heart failure in patients with AMI after percutaneous coronary intervention (PCI), 148 patients were randomly assigned (85 to sacubitril/valsartan and 63 to valsartan). Results LAV, LVDV, and LVSV were all decreased in the sacubitril/valsartan group when compared with before treatment, but there was no difference between the sacubitril/valsartan group and the valsartan group. In addition, compared with before treatment in the sacubitril/valsartan group, the heart global work index (GWI) and the global work efficiency (GWE) increased, while the heart global wasted work (GWW) decreased. Patients in the sacubitril/valsartan group have similar MACE and adverse side effects to those in the valsartan group. Conclusion Sacubitril/valsartan has the same performance as valsartan in inhibiting ventricular remodeling and preventing heart failure after PCI in patients with AMI, and its clinical application is safe. It provides a clinical foundation for the application of sacubitril/valsartan in patients with AMI.